Prevention method preferences and factors influencing hypothetical choice among women in South Africa: a survey exploring opportunities for a multipurpose prevention technology implant - Martin, Catherine E.; Kutywayo, Alison; Mataboge, Paballo; Chidumwa, Glory; Mthimkhulu, Nqaba; Bothma, Rutendo; Mullick, Saiqa (Frontiers in Reproductive Health, 2024)
Introduction South African women bear an intersecting burden of HIV, sexually transmitted infections (STIs) and unintended pregnancy. Multipurpose prevention technologies (MPTs) are a class of products that address multiple needs and have the potential to improve uptake and use of prevention products. Methods Analysing survey data from 703 HIV-negative women 18–40 years in three provinces in South Africa, collected between July and November 2022, this study explores their preferences for prevention methods and factors influencing choice of hypothetical prevention methods, including MPTs. Descriptive statistics and multinomial regression analyses were conducted to determine prevention method preferences and factors associated with choosing a pill, injectable or MPT-implant type prevention method. Results Most women wanted to prevent HIV, STIs and pregnancy. The most important factors when choosing a prevention product were whether it provided dual and long-term protection and if side effects were manageable. If choosing only one method, half of women would choose any MPT-implant and a quarter each would choose a pill or an injectable method, with method choices differing by population group. Discussion Prevention method choices were influenced by sexual-behavioural factors and current and prior contraceptive method use. Providing a choice of prevention methods and a population specific approach to new method development and introduction with access to accurate information could enhance their ability to fill a gap in prevention needs.